Pollination and parasitism in functionally dioecious figs. - Weiblen, G; Yu, D; Wes, SA (2001)
Fig wasps (Agaonidae: Hymenoptera) are seed predators and their interactions with Ficus species (Moraceae) range from mutualism to parasitism. Recently considerable attention has been paid to conflicts of interest between the mutualists and how they are resolved in monoecious fig species. However, despite the fact that different conflicts can arise, little is known about the factors that influence the persistence of the mutualism in functionally dioecious Ficus. We studied the fig pollinator mutualism in 14 functionally dioecious fig species and one monoecious species from tropical lowland rainforests near Madang, Papua New Guinea. Observations and experiments suggest that (i) pollinating wasps are monophagous and attracted to a particular host species; (ii) pollinating and non-pollinating wasps are equally attracted to gall (male) figs and seed (female) figs in functionally dioecious species; (iii) differing style lengths between gall figs and seed figs may explain why pollinators do not develop in the latter; (iv) negative density dependence may stabilize the interaction between pollinating wasps and their parasitoids; and (v) seed figs may reduce the search efficiency of non-pollinators. This increased pollinator production without a corresponding decrease in seed production could provide an advantage for dioecy in conditions where pollinators are limiting.